Screening for Developmental Disorders in 4 to 60 Months Old Children in Iran (2015–2016) - Ahmadipour, Shokoufeh; Mohammadzadeh, Morteza; Mohsenzadeh, Azam; Birjandi, Mehdi; Almasian, Mohammad (Journal of Pediatric Neurology, 2019)
Developmental delay occurs when children fail to reach their developmental milestones at the appropriate time. The aim of this study was to determine the prevalence of developmental disorders as well as their correlations with selected demographic factors affecting development in children 4 to 60 months old in Khorramabad, Iran from 2015 to 2016. In this cross-sectional study, 500 children from 4 to 60 months of age and visiting health service centers were selected. Developmental status was measured using the Ages and Stages Questionnaire, and supplementary data were collected by separate questionnaires. Data were analyzed by the SPSS software using the independent t-test, chi-square test, and Mann–Whitney U test. Note that 8.6% of the children assessed in this study had developmental disorders. The mean age of the children in the normal group was 21.95 ± 16.42 months and in the developmental delay group was 16 ± 13.46 months. The highest prevalence of developmental delay was in the fine motor area (4.2%) and the lowest was in the personal–social area (1.4%). There were correlations between developmental disorder and the child's age (p = 0.006), birth order (p = 0.02), mother's education (p = 0.007), and father's education (p = 0.002). The parents' age, familial marriage, history of developmental disorders in the family, and the child's gender were not correlated with developmental disorders. Due to the high prevalence of developmental disorders and the importance of early identification and intervention, it is necessary to diagnose developmental disorders at early ages.
Keywords: Ages and Stages Questionnaire; children; developmental disorders; early ages